2019
DOI: 10.1038/s41598-019-42680-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression differences between matched pairs of ovarian cancer patient tumors and patient-derived xenografts

Abstract: As patient derived xenograft (PDX) models are increasingly used for preclinical drug development, strategies to account for the nonhuman component of PDX RNA expression data are critical to its interpretation. A bioinformatics pipeline to separate donor tumor and mouse stroma transcriptome profiles was devised and tested. To examine the molecular fidelity of PDX versus donor tumors, we compared mRNA differences between paired PDX-donor tumors from nine ovarian cancer patients. 1,935 differentially expressed ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 44 publications
2
38
0
Order By: Relevance
“…This can result in variability in the expression signal which can be wrongly inferred as CN changes, both from the tumor itself and through cross hybridization of mouse RNA to the human microarray. Although improved concordance in expression between PT and PDX can be achieved with RNA sequencing with the removal of mouse reads 67,68 , we observed that expression-based copy number inferences still have low resolution and robustness. Hence, many cancer-driving genes, which are found mainly in focal events with a size of 3Mb or lower 6972 , cannot be evaluated for PDX-specific alterations.…”
Section: Discussionmentioning
confidence: 79%
“…This can result in variability in the expression signal which can be wrongly inferred as CN changes, both from the tumor itself and through cross hybridization of mouse RNA to the human microarray. Although improved concordance in expression between PT and PDX can be achieved with RNA sequencing with the removal of mouse reads 67,68 , we observed that expression-based copy number inferences still have low resolution and robustness. Hence, many cancer-driving genes, which are found mainly in focal events with a size of 3Mb or lower 6972 , cannot be evaluated for PDX-specific alterations.…”
Section: Discussionmentioning
confidence: 79%
“…Although PDX models retain the majority of the single nucleotide variants (SNVs) in parental tumors, the characteristics of SNVs within xenograft tumors are distinct from those in parental tumors . A previous study established 20 PDX CRC models and detected an increased number of variant alleles within xenograft tumors.…”
Section: Differences In Molecular Characteristics Among Pdx Modelsmentioning
confidence: 99%
“…With regard to 34 PDX‐specific missense mutations, 11 were expressed based on the RNA‐seq results. Two recent studies in ovarian cancer and identified 1,935 and 4,180 genes that are differentially expressed between PDXs and parental tumors, among which 168 and 918 were upregulated in PDX models and 1,767 and 3,262 were downregulated (Table ) …”
Section: Differences In Molecular Characteristics Among Pdx Modelsmentioning
confidence: 99%
“…Primary patient tumour cluster together with PDX tumours clustering together but separate from the primary tumour. RNASeq data in ovarian PDX models demonstrate this differential clustering is predominantly due to the loss of human stroma and the growth of murine stroma [35]. By comparing the adjacent normal to the tumour and the tumour to the F1 PDX tumour we aimed to map the genes associated with tumour growth, proliferation and tumour in engraftment.…”
Section: Discussionmentioning
confidence: 99%